Upaya peningkatan pemahaman konsep geometri dengan media powerpoint interaktif pada siswa kelas 5 - Laili, Azizatun Nurul (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to find out whether there are differences in the learning outcomes of elementary/MI students who are taught mathematics using PowerPoint learning materials. This research uses meta-analysis methodology, which utilizes previous research to inform its findings. The media used for teaching are tools that can facilitate learning. This aims to ensure that this learning resource can help educators and students achieve their learning goals. Learning media is an instrument that can assist in the teaching and learning process, thereby enabling the realization of educational or learning objectives effectively and efficiently as well as a better understanding of the material presented. The aim of this research is to find out how the use of PowerPoint material affects the mathematics learning outcomes of fifth grade students on the material of geometric ideas, plane shapes and space. Research data was collected using Google Scholar to search for journals.